Exploring the Relationship between Logical Reasoning Skills, Scientific Literacy, and Academic Achievement in Science Courses Among Secondary Students: A Mixed Method Study - Winata Tegar Saputra; Nuryani Y. Rustaman; Lilit Rusyati (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the correlation between Scientific Literacy (SL) results from PISA 2015 released items, the Test of Logical Thinking (TOLT), and Science Score Achievement (SSA). The method of this study used an explanatory sequential research design with cross-sectional and convenience sampling. Ninety-two 15-year-old students and science teachers participated. The correlation between SL, TOLT, and SSA was positive but moderately weak. The average SL score was low at 33.04%. TOLT results showed that 64.13% of students demonstrated concrete reasoning, 32.61% proportional reasoning, and 3.26% formal reasoning. SSA scores averaged 81.90, with 53 students scoring above average. Interviews with teachers suggested low SL and LT scores resulted from a lack of hands-on activities, as teachers relied heavily on lectures. Science textbooks also lacked inquiry-based learning tasks. The limitations of this research are that it does not cover gender comparison, school curriculums, or school locations, whether urban or suburban. The psychological aspects regarding the students’ interest or efficacy are not included in the discussion or provided. Also, students with positive learning experiences in science have good results in SL, and TOLT has not been proven empirically.